Traumatismo craneoencefálico pronóstico y complicaciones en el servicio de cirugía del Hospital Isidro Ayora Loja - Monge Núñez, Jossely Nathalia (2021)
Cranioencephalic trauma has been considered one of the most worrisome, serious and mortal pathologies because it involves the central nervous system. The purpose of this study was to establish the prognosis and complications of cranioencephalic trauma in the surgical service of the Hospital Isidro Ayora Loja. A descriptive, retrospective study with a quantitative approach was carried out with a population of 125 patients diagnosed with cranioencephalic trauma during the period August 2017-August 2019. After obtaining the corresponding permissions, data collection forms were filled out for subsequent tabulation and analysis; statistical analysis was performed using the Kolmogorov-Smirnov normality test, the Wilcoxon rank test, and the binary logistic regression method (forward: Wald). There was a higher frequency of cases in the male sex, and the age range with the highest number of cases was between 18 and 26 years, both in men and women. The prognosis is directly related to the pre-discharge score measured by the Glasgow Coma Scale, i.e. it are less likely to die in those with Glasgow Coma Scale values > or equal to 9 and better in those with < or equal to 8 and electrolyte disturbances, followed by intracranial hypertension are the most frequent complications in these patients, while infections, cranial nerve injuries, seizures and post-traumatic epilepsy, cerebrospinal fluid fistula and death occurred less frequently. It should be noted that most of the patients did not present any complications. Key words: cranioencephalic trauma, prognosis, complications.